Review on significance of GDNF, PTCH1 and RNF213 in chromophobe renal cell carcinoma illustrated by the case of 71-years-old man - Kowalik, Artur; Wincewicz, Andrzej; Ossoliński, Krzysztof; Zięba, Sebastian; Kopczyński, Janusz; Ossoliński, Tadeusz; Góźdź, Stanisław; Koda, Mariusz; Sulkowski, Stanisław (Polish Journal of Pathology, 2020)
Here we review the role of GDNF, PTCH1, RNF213 illustrated by a case of renal cell carcinoma, chromophobe type (pT2a 8th pTNM edition) of the left kidney of 71-year-old man. Status of potential hotspots in 409 tumor genes were studied by means of next generation sequencing (NGS) technology (IonTorrent – Thermo Fisher Scientific, USA) using Ion AmpliSeq™ Comprehensive Cancer Panel. Next-generation sequencing (NGS) revealed mutations of GDNF (NM_001190468: c. 328C>T, p.R110W, allelic frequency 46%), PTCH1 (NM_001083607:c. 2969C<T, p.A990V, allelic frequency 7%) RNF213 (NM_001256071: c.6967C<T, p.Q2323X, allelic frequency 7%). Our findings in relation to concise description of significance of GDNF, PTCH1, RNF213 supplement molecular characterization in area of gene profiling of renal cell carcinoma, chromophobe type, which is going to certainly deepen our knowledge on hazards in development of this peculiar kind of renal cancer.